Human pluripotent stem cell-based models of heart development and disease - Velichkova, Gabriel; Dobreva, Gergana (Cells & development, 2023)
The heart is a complex organ composed of distinct cell types, such as cardiomyocytes, cardiac fibroblasts, endothelial cells, smooth muscle cells, neuronal cells and immune cells. All these cell types contribute to the structural, electrical and mechanical properties of the heart. Genetic manipulation and lineage tracing studies in mice have been instrumental in gaining critical insights into the networks regulating cardiac cell lineage specification, cell fate and plasticity. Such knowledge has been of fundamental importance for the development of efficient protocols for the directed differentiation of pluripotent stem cells (PSCs) in highly specialized cardiac cell types. In this review, we summarize the evolution and current advances in protocols for cardiac subtype specification, maturation, and assembly in cardiac microtissues and organoids.